The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1002/chem.200801310
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, Cytotoxicity, and Hydrolytic Behavior of C2‐ and C1‐Symmetrical TiIV Complexes of Tetradentate Diamine Bis(Phenolato) Ligands: A New Class of Antitumor Agents

Abstract: We recently introduced a new class of bis(isopropoxo)-Ti(IV) complexes with diamine bis(phenolato) ligands that possess antitumor activity against colon HT-29 and ovarian OVCAR-1 cells that is higher than that of the known Ti(IV) compounds titanocene dichloride and budotitane as well as that of cisplatin. Herein, we elaborate on this family of compounds; we discuss the effect of structural parameters on the cytotoxic activity and hydrolytic behavior of these complexes, seeking a relationship between the two. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
197
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(224 citation statements)
references
References 50 publications
23
197
3
Order By: Relevance
“…Recent studies by Tshuva and co-workers that utilized catechol as a bidentate substitute for the isopropoxy groups showed a two-fold decrease in the cytotoxicity of the resulting complex. [40] Although the observed effect is significant, an explanation is not evident because not only is the steric influence altered, but also the exchange of the two monodentate isopropoxy groups for one bidentate catecholato ligand leads to a different complex geometry. In the starting complex the isopropoxy groups are oriented in a cis fashion, but the two phenolato substituents of the salan are now occupying their position, which results in a loss of symmetry.…”
Section: Titanium-bound Alkoxidesmentioning
confidence: 91%
See 3 more Smart Citations
“…Recent studies by Tshuva and co-workers that utilized catechol as a bidentate substitute for the isopropoxy groups showed a two-fold decrease in the cytotoxicity of the resulting complex. [40] Although the observed effect is significant, an explanation is not evident because not only is the steric influence altered, but also the exchange of the two monodentate isopropoxy groups for one bidentate catecholato ligand leads to a different complex geometry. In the starting complex the isopropoxy groups are oriented in a cis fashion, but the two phenolato substituents of the salan are now occupying their position, which results in a loss of symmetry.…”
Section: Titanium-bound Alkoxidesmentioning
confidence: 91%
“…For alkyl-substituted salans, it has already been shown that the cell penetration mechanism is independent of transferrin. [40] Remarkably, even though the mechanism of action seems to be different for halogen-sub- 2 ]complexes by using the AlamarBlue assay with Hela S3 and Hep G2 cells. The cells were incubated with the complexes for 48 h prior measurement.…”
Section: Wwwchemeurjorgmentioning
confidence: 98%
See 2 more Smart Citations
“…However, recent advances in titanium-stabilizing ligands have led to a new class of cytotoxic Ti-based antineoplastics 5 . Prominently, introduction of the ligand salan, a diamine bisphenalato compound, conferred excellent hydrolytic stability to Ti(IV) alkoxide complexes, as presented by Tshuva and co-workers (Chart 1, 1) [6][7][8][9][10][11][12][13] . Many of these compounds also demonstrated micro-and submicromolar antiproliferative activity against HT29 and OVCAR-1 cancer cell lines in vitro.…”
Section: ■ Introductionmentioning
confidence: 95%